Identification and Modification of Porphyromonas gingivalis Cysteine Protease, Gingipain, Ideal for Screening Periodontitis - Hirai, Kimito; Yamaguchi-Tomikawa, Tomoko; Eguchi, Toru; Maeda, Hiroshi; Takashiba, Shogo (Frontiers in Immunology, 2020)
Chronic periodontitis is an inflammatory disease caused by the formation of oral microbial biofilms. Periodontitis is associated with general health and not only oral diseases. Porphyromonas gingivalis is a well-known keystone pathogen for periodontitis and is associated with several systemic diseases, such as diabetes mellitus and Alzheimer's disease. We previously developed a system for screening periodontitis using P. gingivalis-specific serum immunoglobulin G (IgG) in an enzyme-linked immunosorbent assay with a sensitivity of 0.774 and a specificity of 0.586 and an area under the receiver operating characteristic curve of 0.708. However, the antigens elicited non-specific responses, since they were obtained from whole extracts of sonicated cultured bacteria. The purpose of this study was to identify antigens ideal for a sensitive and specific serum test. We identified the specific antigens using immunoaffinity columns immobilized with IgG antibodies from periodontitis patients. Liquid chromatography-tandem mass spectrometry identified 29 antigens from the elutes. Recombinant proteins for these candidates were synthesized using the wheat germ cell-free translation system and screened by dot blot analysis with serum from the columns. Three of the 16 candidates that reacted showed strongest affinities upon dot blot analysis; they included outer membrane protein 28, cysteine proteases, lysine gingipain Kgp, and arginine gingipain RgpA. Outer membrane protein 28 was not suitable for screening P. gingivalis infection because of its high false-negative rates. Kgp and RgpA were unstable antigens since they underwent self-digestion. They were made stable by substituting the active cysteine residues in Kgp and RgpA with alanine using site-directed mutagenesis. Using the modified antigens, we demonstrated that the patient serum IgG level against RgpA was the highest among all the antigens expressed in P. gingivalis. Moreover, the N-terminus of recombinant RgpA was excellent in differentiating between diseased and non-diseased states (with sensitivity of 0.85, specificity of 0.9, and area under the curve of 0.915). Although dot blot analysis was the only experiment used, the N-terminus of RgpA is an excellent antigen to immunologically test for P. gingivalis infection, especially for estimating the risks for periodontitis-associated systemic diseases. In conclusion, we have developed a P. gingivalis antigen for screening periodontitis.